The interplay between formal and informal institutions in Turkey: the case of the Fethullah Gülen community. Issue 2 (3rd March 2016) - Başkan-Canyaş, Filiz; Canyaş, F. Orkunt
ABSTRACT: Supporters of the Fethullah Gülen community, an informal institution with an influential role in Turkish political life, have formed an international chain of schools and student dormitories, and a communications web that includes newspapers, journals, television and radio channels, as well as other companies and finance institutions. Although the community has no formal structure, its followers have established these formal institutions to integrate it into formal systems like education and the economy. This paper focuses on the community's educational organizations to argue that, since the community has preferred to pursue its goals within Turkey's existing formal framework, rather than by challenging it or breaking its rules, it can be defined as an accommodating informal institution rather than complementary, competing or substitutive.